Work Ethic and Work Environment on Job Satisfaction: Goal Setting Theory Study - Annasya, Asyifani Luthfiyyah; Sulistiyani, Endang - (Admisi dan Bisnis, 2023)
The purpose of this study was to determine the effect of work ethic and work environment on employee job satisfaction at PT Cempaka Indah Murni Semarang. The respondents of this research are all employees of PT Cempaka Indah Murni Semarang. The sampling technique used is total sample technique. Data were collected through interviews, observations and questionnaires. Data were analysed using the least square technique. The results showed that work ethic and work environment have a significant effect partially and simultaneously on job satisfaction. The work environment has a dominant influence on job satisfaction. The suitability of the work environment, both physical and non-physical, creates a feeling of satisfaction and pleasure with the results of his work